Internalisasi Pendidikan Karakter Melalui Discovery Learning Materi Himpunan Bilangan - Mohammad Kholil; Arbain Nurdin (HMPS PGMI FTIK IAIN Jember, 2022)
The aimed of this study was to determine the effect of internalizing character education through discovery learning on the set of numbers on the character of students at MIN 3 Jember. This study uses a quantitative approach with a quasi-experimental research type with nonequivalent control group design. The experimental group in this study was class IVA which consisted of 28 students, and the control group was class IVB which consisted of 27 students at MIN 3 Jember. The data were obtained from filling in the student character questionnaire. Data analysis uses an independent sample t-test which begins with a prerequisite test in the form of a normality test and homogeneity test. The results showed that tcount = 2.613 > ttable = 2.006, and tcount = 4.979 > ttable = 2.006. This indicates that there are differences in pretest and posttest student character questionnaire scores between the experimental class and the control class. This shows that there is an effect of internalizing character education through discovery learning on set of numbers. Penelitian ini bertujuan mengetahui pengaruh internalisasi pendidikan karakter melalui discovery learning materi himpunan bilangan terhadap karakter siswa MIN 3 Jember. Pendekatan kuantitatif yang dipilih dengan jenis penelitian kuasi eksperimen serta desain nonequivalent control group. Kelompok eksperimen dalam penelitian ini adalah kelas IVA yang terdiri dari 28 siswa, dan kelompok kontrol adalah kelas IVB yang terdiri dari 27 siswa MIN 3 Jember. Data diperoleh dari isian angket karakter siswa. Analisis data menggunakan uji-t sampel independen yang diawali dengan uji prasyarat berupa uji normalitas dan uji homogenitas. Hasil penelitian menunjukkan bahwa thitung = 2,613 > ttabel = 2,006, dan thitung = 4,979 > ttabel = 2,006. Ini mengindikasikan adanya perbedaan skor angket karakter siswa pretest dan posttest antara kelas eksperimen dan kelas kontrol. Data ini menunjukkan bahwa ada pengaruh internalisasi pendidikan karakter melalui discovery learning materi himpunan bilangan.